Influence of media (internet and smartphone applications) on infant and young child feeding practices among mothers of children under 5 years availing health care in a rural hospital in Ramanagara district, Karnataka - Vinshula, Joeberate; Johnson, Avita; Joseph, Merlyn; Menezes, Anna Rachel; C, Srilekha; S, Priya; Jennifer, Jessi (Indian Journal of Child Health, 2022)
Background: Appropriate infant and young child feeding (IYCF) practices are a key strategy to reduce under-5 mortality. Increasing mobile technology penetration in rural areas can influence IYCF practices. Aims: This study aims to assess IYCF practices among mothers of children under 5, in a rural maternity hospital in Ramanagara district and its association with the use of various mass media including internet and smartphones. Methods: A hospital-based cross-sectional study was conducted among 89 mothers and a pre-tested face-validated semi-structured interview schedule was administered to collect information regarding sociodemographic details, IYCF practices, and use of media. Results: The mean age of the study population was 23.84±3.5 years. About 44.9% of them had their last child in the age group of 6–24 months. About 87.6% of them were breastfed within the 1st h of birth. The mean age of starting complementary feeding was 7±2.6 months. About 98.9% had access to a smartphone, however, only 19.1% used WhatsApp videos and messages and 12.3% internet to search for information regarding IYCF practices. Almost all respondents reported health-care providers as their primary source of information regarding IYCF practices. Conclusion: IYCF practices of the study population were better than national average. These findings highlight the importance of the role of grassroot level workers and primary care physicians in imparting knowledge among mothers in IYCF practices. The scope of using media to bring about behavior change communication in this context can be explored.